Manejo del tepezcuintle en criaderos - Fernández, Alejandra; Pachov, Blagovesta (San José, [C.R.] : [editor no identificado], 1990)
Resume la explotación de la crianza de tepezcuintles en criaderos
Keywords: TEPEZCUINTLES